Nurse’s Experiences and Perceptions of Complementary and Alternative Therapies for Workplace Stress Management - Zakarian, Melissa (2012)
Nursing as a profession has been said to be one of high stress, high sickness absence and presenteeism at work. Complementary and Alternative therapies are continually being researched for their benefits in relieving stress. To target these stress levels NHS Trusts have put into practice workplace wellness schemes, however nurses do not seem to be accessing them. Therefore this qualitative study aimed to discover Nurse’s Experiences and Perceptions of Complementary and Alternative Therapies for Workplace Stress Management. Semi-structured interviews were conducted with 12 registered nurses working within the emergency department and the burns high dependency unit. Key themes that emerged were that nurses acknowledge that they experience high levels of stress at work and they to need to better manage their stress. All the nurses had some experience of using complementary and alternative therapies outside of the workplace and they found them to be relaxing and stress relieving. However they were not able to access workplace wellness services that offered Complementary and Alternative therapies because they work long hours and have very short breaks and most were not even aware that any services were offered by their Trust. They described the main barriers to access as cost, time and location. This study highlighted the need for more advertising about services offered by Trusts providing Complementary and Alternative therapies and a change in service times to allow nurses better access.